S-Nitrosylation Induces Structural and Dynamical Changes in a Rhodanese Family Protein. Issue 19 (25th September 2016) - Eichmann, Cédric; Tzitzilonis, Christos; Nakamura, Tomohiro; Kwiatkowski, Witek; Maslennikov, Innokentiy; Choe, Senyon; Lipton, Stuart A.; Riek, Roland
Abstract: S-Nitrosylation is well established as an important post-translational regulator in protein function and signaling. However, relatively little is known about its structural and dynamical consequences. We have investigated the effects of S-nitrosylation on the rhodanese domain of the Escherichia coli integral membrane protein YgaP by NMR, X-ray crystallography, and mass spectrometry. The results show that the active cysteine in the rhodanese domain of YgaP is subjected to two competing modifications: S-nitrosylation and S-sulfhydration, which are naturally occurring in vivo . It has been observed that in addition to inhibition of the sulfur transfer activity, S-nitrosylation of the active site residue Cys63 causes an increase in slow motion and a displacement of helix 5 due to a weakening of the interaction between the active site and the helix dipole. These findings provide an example of how nitrosative stress can exert action at the atomic level. Graphical Abstract: Highlights: S-nitrosylation is a common protein modification, but its impact on structure and dynamics is not well understood. The rhodanese domain of YgaP has a rhodanese-typical conformation of the active loop with the catalytic cysteine sandwiched between the N termini of α4 and α5 helices. S-nitrosylation and S-sulfhydration are competing processes in YgaP and both are present when YgaP is overexpressed in E. coli . S-sulfhydration destabilizes helix α4, but under nitrosative stress, the balance shifts toward S-nitrosylation, which induces the slow dynamics of helix α5 while stabilizing α4.